Mercury exposure may influence fluctuating asymmetry in waterbirds. (6th January 2017) - Herring, Garth; Eagles‐Smith, Collin A.; Ackerman, Joshua T.
Abstract: Variation in avian bilateral symmetry can be an indicator of developmental instability in response to a variety of stressors, including environmental contaminants. The authors used composite measures of fluctuating asymmetry to examine the influence of mercury concentrations in 2 tissues on fluctuating asymmetry within 4 waterbird species. Fluctuating asymmetry increased with mercury concentrations in whole blood and breast feathers of Forster's terns ( Sterna forsteri ), a species with elevated mercury concentrations. Specifically, fluctuating asymmetry in rectrix feather 1 was the most strongly correlated structural variable of those tested (wing chord, tarsus, primary feather 10, rectrix feather 6) with mercury concentrations in Forster's terns. However, for American avocets ( Recurvirostra americana ), black‐necked stilts ( Himantopus mexicanus ), and Caspian terns ( Hydroprogne caspia ), the authors found no relationship between fluctuating asymmetry and either whole‐blood or breast feather mercury concentrations, even though these species had moderate to elevated mercury exposure. The results indicate that mercury contamination may act as an environmental stressor during development and feather growth and contribute to fluctuating asymmetry of some species of highly contaminated waterbirds. Environ Toxicol Chem 2017;36:1599–1605. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.